An Analysis of Mathematical Critical-Thinking Ability: The Impact of DCT (Dialogue Critical Thinking) and Learning Motivation - Nahdiyah, zuhan; netriwati, netriwati; Anggraini, Dian; Nendra, Fadly (Desimal: Jurnal Matematika, 2020)
The mathematical critical thinking ability is part of a very important mathematical curriculum. The purpose in this study was to analyze the influence of Deep DCT Learning and the motivation to learn from the mathematical critical thinking ability. Research in is a quantitative study with the type of Quasy experimental Design by using post-test only control. Sampling techniques are performed by means of Random Sampling. Data retrieval is done by giving post-Test and poll. The analysis test used is a two way variances analysis (ANAVA). Based on the research results analyzed that: There is an influence between Deep DCT Learning to the mathematical critical thinking ability, there is a high, moderate and low motivation influence on mathematical critical thinking Skills, There is no interaction between Deep DCT Learning and the motivation to learn the ability of critical thinking mathematically.